Ashwagandha: Potential Integrative Management of Tuberculosis - Bandale, Dr. Mukund Baburao; Baheti, Dr. Sandipkumar Ramjivan (International Journal of Innovative Research in Medical Science, 2020)
The World Health Organization TB (Tuberculosis) statistics for India for 2018 give an estimated incidence of 2.69 million cases.TB is being a challenge for India and worldwide developing countries pre and post antitubercular drug era. The major limitations clinicians face in management of TB is its MDR, immunosuppression, bad prognosis during course of treatment and associated side effects of anti- tubercular drugs putting patient in danger for multiple organ failure. The presence of comorbidities, nutritional deficiencies add up toll in the whole clinical presentation of tuberculosis management. There is very systematic pathophysiology and treatment ideology explained in Ayurveda for tuberculosis and related respiratory infections. There is great need to integrate Ayurveda wisdom of understanding tuberculosis and medicinal herbs in protective mode with aggressive targeted anti TB activity of modern medicine. Ashwagandha is strong Rasayana category medicinal plants with ancient references for its beneficial effect in management of tuberculosis also supported by modern day in vitro, in vivo and clinical evidences of effectiveness of Ashwagandha in management of tuberculosis could be ray of hope. There should focused research aimed at unfolding mechanisms and clinical guidelines for the use of Ashwagandha as an adjuvant in themanagement of tuberculosis.